MERIT SYSTEM DALAM MEWUJUDKAN TRANSPARANSI PEMBINAAN KARIER APARATUR SIPIL NEGARA - Nurwita Ismail (Al-Adl : Jurnal Hukum, 2019)
AbstractThe Merit System is a reflection of professional staffing management where the placement of employees and officials uses performance competencies and track records as a means of measuring appointments. But so far the system merit has not been fully implemented even though if this system is implemented, it can produce qualified official figures and have good performance other than that it will not interfere with internal conditions because it has continuity with the old officials. Practices that occur are politicization of the State Civil Apparatus. Merit violations are usually like people being demoted without clear reasons and mutations. New regional heads usually dismantle their employees with people he knows. Everything is still related to retribution and revenge, so that this article is carried out with the aim of knowing how the implementation of the Merit System in ASN career development and the factors that influence the implementation of Merit System can realize the transparency of ASN career coaching using Qualitative analysis methods. So that it is expected to contribute ideas to the government in the study and implementation of a better Merit System. Keywords: Merid System and State Civil Apparatus AbstrakMerit sistem merupakan cerminan manajemen kepegawaian yang profesional dimana penempatan pegawai dan pejabat menggunakan kompetensi kinerja dan track record sebagai alat ukur pengangkatan. Namun sejauh ini merit sistem belum sepenuhnya dilakukan padahal Jika sistem ini diterapkan, dapat menghasilkan figur pejabat yang mumpuni dan memiliki kinerja bagus selain itu tidak akan mengganggu kondisi internal karena memiliki kesinambungan dengan pejabat lama. Praktek-praktek yang terjadi adanya politisasi terhadap Aparatur Sipil Negara. Pelanggaran Merit itu biasanya seperti orang diturunkan jabatannya tanpa alasan yang jelas dan mutasi. Kepala daerah baru biasanya membongkar pegawainya dengan orang-orang yang dia kenal. Semuanya masih berkaitan dengan balas budi dan balas dendam, sehingganya tulisan ini dilakukan dengan tujuan mengetahui Bagaimana implementasi Merit System dalam  pembinaan karier ASN serta Faktor yang mempengaruhi penerapan Merit System dapat mewujudkan transparansi pembinaan karier ASN dengan menggunakan Metode analisis Kualitatif. Sehingga diharapkan dapat memberikan sumbangan pemikiran terhadap pemerintah dalam pengkajian dan pelaksanaan Merid Sytem kearaha yang lebih baik. Kata Kunci: Merid System, Aparatur Sipil Negara